A New FOC Approach of Induction Motor Drive Using DTC Strategy for the Minimization of CMV - Kola Satya Narayana; P. Surekha; P.Vijaya Prasuna (Institute of Advanced Engineering and Science, 2013)
This paper presents a New FOC Approach of Induction Motor Drive using DTC Strategy for the Minimization of CMV (common mode voltage) with the switching tables for the generation of PWM signals. High performance induction motor drives require a better transient and steady state performance. To achieve high performance, there are two control strategies namely, field oriented control (FOC) and direct torque control (DTC) for induction motor drives. Though these two methods give better transient performance, the FOC needs reference frame transformations and DTC gives large steady state ripples. To overcome these drawbacks, this paper presents a novel FOC algorithm for induction motor drives, which combines the principles of both FOC and DTC. The proposed method uses a predetermined switching table instead of a much more time consuming pulse width modulation (PWM) procedure. This approach gives a quick torque response like DTC and gives reduced ripple like FOC. The switching table is based on the conventional DTC principle, which gives good performance with reduced common mode voltage variations. To validate the proposed method numerical simulations have been carried out and compared with the existing algorithms. The simulation results confirm the effectiveness of the proposed method. DOI: http://dx.doi.org/10.11591/ijpeds.v3i2.2416